Graphical Workflow System for Modification Calling by Machine Learning of Reverse Transcription Signatures - Schmidt, Lukas; Werner, Stephan; Kemmer, Thomas; Niebler, Stefan; Kristen, Marco; Ayadi, Lilia; Johe, Patrick; Marchand, Virginie; Schirmeister, Tanja; Motorin, Yuri; Hildebrandt, Andreas; Schmidt, Bertil; et al. (Frontiers in Genetics, 2019)
Modification mapping from cDNA data has become a tremendously important approach in epitranscriptomics. So-called reverse transcription signatures in cDNA contain information on the position and nature of their causative RNA modifications. Data mining of e.g. Illumina-based high throughput sequencing data is therefore fast growing in importance, and the field is still lacking effective tools. Here we present a versatile user-friendly graphical workflow system for modification calling based on machine learning. The workflow commences with a principle module for trimming, mapping and post-processing. The latter includes a quantification of mismatch and arrest rates with single nucleotide resolution across the mapped transcriptome. Further downstream modules include tools for visualization, machine-learning, and modification calling. From the machine-learning module, quality assessment parameters are provided to gauge the suitability of the initial dataset for effective machine learning and modification calling. This output is useful to improve the experimental parameters for library preparation and sequencing. In summary, the automation of the bioinformatics workflow allows a faster turnaround of the optimization cycles in modification calling.